Perfil volátil das tangerinas murcott (Citrus reticulata x Citrus sinensis) e ponkan (Citrus reticulata Blanco) por SPME e SBSE - Siqueira, Airla Carla Pires de (2019)
Brazil is the largest producer of citrus fruits, being the main products of the agroindustrial export chain. The cultivation of powdered fruit is a second blend between citrus and flexible varieties such as room temperature. The consumption of tangerine is much appreciated by Brazilians in its fresh form, having a refreshing predominance and a great nutritional value, since it is rich in vitamins and fibers. There are different varieties of tangerine around the world, being two popularily consumed varieties of Ponkan and Murcott. However, no papers have been published that analyzed the volatile constituents of fruits of these varieties. Thus, this work was undertaken to determine the volatile compounds of the pulp of two varieties of tangerine: Poncán and Murcott by gas chromatography using the SPME (Solid Phase Micro-Extraction) e SBSE (Stir Bar Sorptive Extraction). Pulp extraction was carried out from mature fruits of the two varieties. The chemical analyses were performed for moisture, ash, lipids, pH, proteins, total acidity and soluble solids, according to the analytical norms of the Adolfo Lutz Institute. Two volatiles extraction procedures were by the SPME and SBSE technique using two phases of twisters (PDMS and EG silicone). A National Institute of Standards and Technology (NIST) database was used for the identification of the compounds. The two pulps differed in pH, acidity, solids content, lipids, ash, ratio and moisture. For the analysis of volatiles, 52 and 67 compounds were identified by SPME with the largest area of D limonene (69.837%) and γ-terpinene (10.792%) for Ponkan and D-linomeno (90.17% for a Murcott The SBSE technique extracted by using twister PDMS with a tangerine and 68 and 102 compounds in the submerged and headspace modes, respectively. The highest concentrations of volatile compounds detected by the SBSE technique were D-limonene (45-75%), linalool (10-25%), and α-terpineol (2-10%) for all twisters in the two mandarin varieties. It was concluded that the work of a more efficient technique was a SBSE with a PDMS extraction phase, for a good recovery of volatile compounds, mainly in the Ponkan variety.